2021
DOI: 10.1186/s43094-021-00288-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic predictions and docking studies of substituted aryl amine-based triazolopyrimidine designed inhibitors of Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH)

Abstract: Background The sixteen (16) designed data set of substituted aryl amine-based triazolopyrimidine were docked against Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH) employing Molegro Virtual Docker (MVD) software and their pharmacokinetic property determined through SwissADME predictor. Results The docking studies shows compound D16, 5-((6-methoxy-5-methyl-[1,2,4]triazolo[1,5-a]pyrimidin-7-yl)amino)benzo[b]thiophen-4-ol to be the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The value of Gibbs free energy of solvation is derived from the ratio of Generalized-born (GB) parameters and solvent-accessible surface area in water/n-octanol (SA) (GB/SA). The iLOGP values for all the phytochemicals in this work, with exceptions to a few compounds (Stigmasterol, Beta-carotene, β-Cryptoxanthin, Lutein), were found to meet the recommended value (less than 5) (Ibrahim et al 2021 ). The extra cellular efflux of a wide range of structurally unrelated drugs is mediated by membrane-bound transporter PGP (P-glycoprotein).…”
Section: Resultsmentioning
confidence: 68%
“…The value of Gibbs free energy of solvation is derived from the ratio of Generalized-born (GB) parameters and solvent-accessible surface area in water/n-octanol (SA) (GB/SA). The iLOGP values for all the phytochemicals in this work, with exceptions to a few compounds (Stigmasterol, Beta-carotene, β-Cryptoxanthin, Lutein), were found to meet the recommended value (less than 5) (Ibrahim et al 2021 ). The extra cellular efflux of a wide range of structurally unrelated drugs is mediated by membrane-bound transporter PGP (P-glycoprotein).…”
Section: Resultsmentioning
confidence: 68%
“…Also, topological polar surface area (TPSA) and the number of rotatable bonds are other critical properties that have been linked to drug bioavailability 74 . The reports suggested that compounds with a TPSA of more than 140 Å2 and more than ten rotatable bonds are thought to have low pharmacological flexibility and permeability, respectively 75 .…”
Section: Resultsmentioning
confidence: 99%
“…The molar refractivity (MR) value should be between 40 and 130 for good absorption and oral bioavailability. Acceptable molar refractivity values, in combination with the number of rotatable bonds, indicate that substances have adequate intestinal absorption and oral bioavailability 75 . Only compound 16a showed accepted MR = 126.21 m 3 /mol, but the remaining designed compound’s MR values ranging from 140.63 to 167.57 m 3 /mol, compared to the standard dasatinib (MR = 133.62 m 3 /mol).…”
Section: Resultsmentioning
confidence: 99%
“…Both parameters are related to oral absorption capacity, and their role in medicinal chemistry has recently increased. [70] In this case, citric acid shows a greater number of hydrogen bonding sites and a higherTPSA value, indicative of greater polarity, which is slightly higher than the limit (130 Å 2 ). The rest of the studied chemicals show values in the polarity range, and choline chloride is the molecule with the lowest TPSA.…”
Section: Physicochemical Properties Solubility and Lipophilicity By S...mentioning
confidence: 86%
“…TPSA correlates with the hydrogen bonds that the molecule can establish. Both parameters are related to oral absorption capacity, and their role in medicinal chemistry has recently increased [70] . In this case, citric acid shows a greater number of hydrogen bonding sites and a higherTPSA value, indicative of greater polarity, which is slightly higher than the limit (130 Å 2 ).…”
Section: Discussionmentioning
confidence: 99%